Pregnancy Outcome in Patients with Placenta Praevia with Delayed Child Bearing Age (TAJ: Journal of Teachers Association, 2020)
This is a hospital-based cross sectional descriptive study was carried out during January 2015 to June 2015 in the Department of Obstetrics and Gynaecology of Rajshahi Medical College Hospital to determine pregnancy outcome in placenta praevia cases with delayed child bearing age.  Total 8107 patients were admitted during the study period and among them 82 patients were diagnosed as placenta praevia. Patients were categorized into two groups as above 35 years & below 35 years and relationship between advanced maternal age and placenta praevia was seen. Socio-demographic condition, clinical condition, course of management, maternal and perinatal outcome were observed and recorded.  Proportion of placenta praevia was 1.01% during the study time. Among 82 patients of placenta praevia, 25 were advanced maternal age group (30.49%). Prevalence of placenta praevia in advanced maternal age group in comparison to below 35 years among total admitted patient was seen 9.73% and 0.73% respectively. So, incidence is more in advanced maternal age group which is statistically significant (p